SiC porous structures obtained with innovative shaping technologies. Issue 3 (March 2018) - Ferraro, Claudio; Garcia-Tunon, Esther; Barg, Suelen; Miranda, Miriam; Ni, Na; Bell, Robert; Saiz, Eduardo
Abstract: SiC structures with porosities ranging between 20–60% have been fabricated using two methods emulsification and freeze casting. While emulsification results in foam-like isotropic materials with interconnected pores, freeze casting can be used to fabricate highly anisotropic materials with characteristic layered architectures. The parameters that control the pore size and final porosity have been identified (solid content in the initial suspensions, emulsification times or speed of the freezing front). We have found that liquid state sintering (suing Al2 O3 and Y2 O3 as additives) at 1800 °C on a powder (SiC/Al2 O3 ) bed provides optimum consolidation for the porous structures. The mechanical strength of the materials depends on their density. Freeze casted materials fabricated with bimodal particle size distributions (a controlled mixture of micro and nanoparticles) exhibit higher compressive strengths that can reach values of up to 280 MPa for materials with densities of 0.47.